2005
DOI: 10.1128/mcb.25.15.6603-6616.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial Ribosomal Protein L41 Suppresses Cell Growth in Association with p53 and p27Kip1

Abstract: The p53 protein arrests the cell cycle at the G 1 phase when stabilized by the interaction between ribosomal proteins and HDM2 under growth-inhibitory conditions. Meanwhile, p53, when translocated to the mitochondria in response to cell death signals, induces apoptosis via transcription-independent mechanisms. In this report, we demonstrate that the mitochondrial ribosomal protein L41 (MRPL41) enhances p53 stability and contributes to p53-induced apoptosis in response to growth-inhibitory conditions such as ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 23 publications
(43 reference statements)
3
76
1
Order By: Relevance
“…The observation made by Waxman and Wurmbach 13 on stable expression of RPL41 in hepatocellular carcinoma varies from the findings by others, 14,15 and those of ours, which suggest its deregulation in cancer cells. In collaboration with p53 and p27 kip1 , it was found to exert tumor-suppressive effects.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The observation made by Waxman and Wurmbach 13 on stable expression of RPL41 in hepatocellular carcinoma varies from the findings by others, 14,15 and those of ours, which suggest its deregulation in cancer cells. In collaboration with p53 and p27 kip1 , it was found to exert tumor-suppressive effects.…”
Section: Discussioncontrasting
confidence: 77%
“…In collaboration with p53 and p27 kip1 , it was found to exert tumor-suppressive effects. 15 Therefore, its downregulation in tumors may suggest loss of control on p53 and p27 kip1 , and inhibition of apoptosis. This phenomenon and the instability of RPL41 in cancer cells of NPC remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…11 Finally, MRPL41 is a mitochondrial ribosomal protein and has an important role in cell growth suppression in association with p53 and p27Kip1. 24 It is not clear how this ribosomal protein may be involved in the etiology of SZ. As the MHC region is overrepresented in the PGC SZ GWAS findings, we were concerned about a possible bias in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have shown that various ribosomal proteins can regulate p53 and apoptosis through several mechanisms, including inhibition of Mdm2, enhancing p53 translation and enhancing p53 translocation to mitochondria (Lohrum et al, 2003;Zhang et al, 2003;Bhat et al, 2004;Jin et al, 2004;Takagi et al, 2005;Yoo et al, 2005), none of ribosomal proteins has been RPS27L silencing inhibits caspase-3 activation: HCT116 cells infected with lenti-virus expressing the control siRNA (con-siRNA) or RPS27L siRNA were subjected to etoposide treatment at various drug concentrations for 24 h, followed by caspase-3 activity assay. The results of X7s.e.m.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p53 translation can be enhanced by ribosomal protein L26 (Takagi et al, 2005). Finally, a mitochondrial ribosomal protein L41 can directly bind to p53 and enhance translocation of p53 to the mitochondria, thus contributing to p53-induced apoptosis (Yoo et al, 2005). Our effort, through the chip profiling of entire human transcriptome for genes responsive to p53-induced growth arrest and apoptosis, led to identification of a novel ribosomal protein, RPS27L as a putative p53-inducible gene (Robinson et al, 2003;Sun, 2006).…”
Section: Introductionmentioning
confidence: 99%